Assessment of the impact of manufacturing changes on the physicochemical properties of the recombinant vaccine carrier ExoProtein A. Issue 38 (10th September 2019) - Burkhardt, Martin; Reiter, Karine; Nguyen, Vu; Suzuki, Motoshi; Herrera, Raul; Duffy, Patrick E.; Shimp, Richard; MacDonald, Nicholas J.; Olano, L. Renee; Narum, David L.
Highlights: ExoProtein A is a carrier protein for conjugate vaccines. Improved purification process yields comparable quantity of bulk EPA. Improved purification process yields bulk EPA with a better purity profile. Immunogenicity of EPA derived original and improved process appear highly similar. Abstract: Efforts to develop a vaccine for the elimination of malaria include the use of carrier proteins to assemble monomeric antigens into nanoparticles to maximize immunogenicity. Recombinant ExoProtein A (EPA) is a detoxified form of Pseudomonas aeruginosa Exotoxin A which has been used as a carrier in the conjugate vaccine field. A pilot-scale process developed for purification of EPA yielded product that consistently approached a preset upper limit for host cell protein (HCP) content per human dose. To minimize the risk of bulk material exceeding the specification, the purification process was redeveloped using mixed-mode chromatography resins. Purified EPA derived from the primary and redeveloped processes were comparable following full biochemical and biophysical characterization. However, using a process specific immunoassay, the HCP content was shown to decrease from a range of 0.14–0.24% w/w of total protein to below the level of detection with the revised process. The improved process reproducibly yields EPA with highly similar quality characteristics as the original process but with an improved profile for the HCP content.